EAACI Position Paper on assessment of cough in the workplace. Issue 3 (15th January 2014) - Moscato, G.; Pala, G.; Cullinan, P.; Folletti, I.; Gerth van Wijk, R.; Pignatti, P.; Quirce, S.; Sastre, J.; Toskala, E.; Vandenplas, O.; Walusiak‐Skorupa, J.; Malo, J. L.
Abstract Cough is a nonspecific and relatively common symptom that can present difficulties in diagnosis and management, particularly when it is reported to be associated with the workplace. The present consensus document, prepared by a taskforce of the Interest Group on Occupational Allergy of the European Academy of Allergy and Clinical Immunology by means of a nonsystematic review of the current literature, is intended to provide a definition and classification of work‐related chronic cough (WRCC) to assist the daily practice of physicians facing with this symptom. The review demonstrates that several upper and lower airway work‐related diseases may present with chronic cough; hence, the possible link with the workplace should always be considered. Due to the broad spectrum of underlying diseases, a multidisciplinary approach is necessary to achieve a definite diagnosis. Nevertheless, more epidemiological studies are necessary to estimate the real prevalence and risk factors for WRCC, the role of exposure to environmental and occupational sensitizers and irritants in its pathogenesis and the interaction with both upper and lower airways. Finally, the best management option should be evaluated in order to achieve the best outcome without adverse social and financial consequences for the worker.